WHAT CONTRIBUTES TO MEMORY LOSS IN EPILEPTIC PATIENTS?. Issue 10 (9th September 2014) - Bray, Emma; Powell, Rob
Abstract : This study was designed to assess rates of memory loss in epileptic patients, and identify potential trends. The method involved a cross-sectional study involving 47 patients aged 16–68, known to have epilepsy. While attending out-patient epilepsy clinics in two district general hospitals, subjects completed 2 memory assessments: one objective and one subjective. The data showed statistically significant correlation between the two scores. Lower objective scores were seen if patients were on multiple drug therapy, or if their seizure frequency was greater. In conclusion, a patient's subjective account of their memory loss does correlate with their score on an objective assessment tool. The results showed that, the greater the number of anti-epileptic medications a patient was taking, the greater the severity of memory impairment. Furthermore, the subjects taking Carbamazepine scored lower objectively.